THE The Effect of The Problem Based Learning Model Using Quizizz Evaluation on Student’s Cognitive Science Learning Outcomes in Elementary School - ZUHARA, NAFISA RISMA; Imam Supardi, Kasmadi; Susilaningsih, Endang (Journal of Primary Education, 2020)
Cognitive learning outcomes of elementary school students are still less than optimal. The learning process still used conventional models with lectures, questions and answers, taking notes, listening, and giving assignments. The teacher still uses the lecture method by cramming various concepts of science into a system of listening, note taking, and memorizing. The purpose of this study was to analyze the effect of the Problem Based Learning’s model using Quizizz evaluation on student cognitive learning outcomes and to determine the difference in the effect of the Problem Based Learning’s model using Quizizz evaluation with conventional learning on student cognitive learning outcomes. The approach used a a quantitative research, namely a quasi-experimental method. The research design used a pretest-posttest control group design. This design involved two groups of subjects, one was given experimental treatment (experimental group) and the other was not given treatment (control class). The results was the Problem Based Learning’s model using Quizizz evaluation affects students' cognitive learning outcomes and there are differences in student cognitive learning outcomes between the experimental class and the control class. In conclusion, the Problem Based Learning’s model using Quizizz evaluation has a positive impact on cognitive learning outcomes of fifth grade students of SDIT Al-Madina